107k views
5 votes
Which equation is y=-6x2 + 3x + 2 rewritten in vertex form?

O y=-6(x-1)2+8
O y =
+
13
8
y=-8(x+4)
y=-6-
2
O y=-6 -
19
8
Y=
X-
7
2

Which equation is y=-6x2 + 3x + 2 rewritten in vertex form? O y=-6(x-1)2+8 O y = + 13 8 y-example-1

1 Answer

4 votes

Answer:

The vertex form of the equation is:


y=-6\,(x-(1)/(4))^2+(19)/(8)

Explanation:

In order to write the equation in vertex form, we need to find the vertex coordinates. The x-coordinate of the vertex of a parabola of the form:


y=ax^2+bx+c

is given by:


x_(vertex)=(-b)/(2\,a)

which in our case renders:


x_(vertex)=(-b)/(2\,a)\\x_(vertex)=(-3)/(-12)\\x_vertex=(1)/(4)

Knowing this, then the y-coordinate of the vertex is obtained by using the x-coordinate of the vertex in the functional form:


y=-6\,((1)/(4)) ^2+3\,((1)/(4) )+2=(19)/(8)

Then, the equation of the parabola in vertex form becomes:


y=a\,(x-(1)/(4))^2+(19)/(8)

Now we need to find the value of the parameter
, which since it is the actual leading term of the function in standard form, should be "-6".

Then the vertex form of the equation is:


y=-6\,(x-(1)/(4))^2+(19)/(8)

User John Riehl
by
5.1k points